WATER, ENERGY AND ENVIRONMENT IN EURASIA - Tanrisever, Oktay F.; Sakal, Halil Burak (Politics Books, 2022)
The Eurasian region has been characterized by growing water, energy and environmental challenges. This book intends to provide answers to the following key questions: What are the major conceptual issues with regards to the water, energy and environment nexus in Eurasia? What are the key challenges and drawbacks faced by the countries in the Eurasian region in responding to the nexus issues? How could regional cooperation be developed so as to mitigate nexus-related sustainability problems? What are the future implications of the current challenges for the regional and global environment? This book highlights the analytical benefits of employing the nexus approach in studying the complex dynamics of water, energy and environment in Eurasia. The nexus approach assumes that the inversely-related interdependency between energy and the environment is more evident in water-related issues. The book brings together the original academic contributions of distinguished experts who have been studying various aspects of the nexus of water, energy and the environment in the Eurasian region from technical and socio-economic to diplomatic aspects. The book is composed of three parts which explore these issues systematically in terms of the employed conceptual framework and the levels of analysis: The first part elaborates on the conceptual framework, the second part focuses on the national level of analysis, while the last part deals with the regional level of analysis.